Epworth League Institute at Coolidge Redwood Grove - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of attendees at the Epworth League Institute. Some attendees hold signs that indicate the city or oranization they represent. These signs reference the following: "Salinas, Hollister, San Mateo, Lodi, and the San Jose Seekers of First Church." The name Coolidge Redwood Grove eventually changed to Underwood Park.